PENGARUH PARTISIPASI ANGGOTA, LINGKUNGAN USAHA DAN STRUKTUR PENGENDALIAN INTERN TERHADAP KEBERHASILAN USAHA KOPER - Muhammad Rofiq Sunarko, Tovia Hotma Alinda, Suharno & (Universitas Slamet Riyadi, 2017)
The purpose of this study is to analyze the effect of participation of members,business environment and internal control structure to the business success of KPRIin Surakarta. This type of research is a survey on KPRI employees in Surakarta.Sampling technique used purposive sampling with sample counted 31 people.Methods of data collection used questionnaires and literature study. Data analysistechniques use multiple linear regression. The results showed that the participationof members has a positive and significant impact on the business success of KPRI inSurakarta. The business environment has a positive and significant effect on thebusiness success of KPRI in Surakarta. Internal control structure has a positive andsignificant effect on the business success of KPRI in Surakarta.Keywords: participation of members, business environment, internal controlstructure, business success.